Designing a Dashboard Application as a Media Monitoring the Performance of a Steam Power Plant at PT Cahaya Fajar Kaltim - Sugiarto, Indra; Lemantara, Julianto; Hananto, Valentinus Roby (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2019)
PT Cahaya Fajar Kaltim is a company engaged in the field of Steam Power (PLTU) resources in East Kalimantan Province. The problem is the Engineering Department has difficulty in evaluating the engine. Problems including recording maintenance of vibration checks have not been computerized so that reports related to recording are often found to be empty, recapitulation related to reports take a long time, and evaluations regarding machine performance cannot be traced in real time. Based on the above problems, the solution needed is an application that can assist the maintenance management process, including recording vibration checks, recording machine maintenance, and visualizing information in the form of dashboards related to engine performance. Based on the evaluation results, the application is able to help record maintenance of vibration checks in a computerized, the report recap can be done quickly, evaluations related to engine performance can be maximized with a dashboard that has machine status notification features, abnormal status engine notifications, and graphical dashboards that check display information in real-time.